Fast and noninvasive characterization of suspicious lesions detected at breast cancer x-ray screening: capability of diffusion-weighted MR imaging with MIPs - Bickelhaupt, Sebastian; Laun, Frederik B.; Tesdorff, Jana; Stieber, Anne; Delorme, Stefan; Schlemmer, Heinz-Peter (Radiology, 2015)
PurposeTo evaluate the ability of a diagnostic abbreviated magnetic resonance (MR) imaging protocol consisting of maximum intensity projections (MIPs) from diffusion-weighted imaging with background suppression (DWIBS) and unenhanced morphologic sequences to help predict the likelihood of malignancy on suspicious screening x-ray mammograms, as compared with an abbreviated contrast material-enhanced MR imaging protocol and a full diagnostic breast MR imaging protocol.Materials and MethodsThis prospective institutional review board-approved study included 50 women (mean age, 57.1 years; range, 50-69 years), who gave informed consent and who had suspicious screening mammograms and an indication for biopsy, from September 2014 to January 2015. Before biopsy, full diagnostic contrast-enhanced MR imaging was performed that included DWIBS (b = 1500 sec/mm2). Two abbreviated protocols (APs) based on MIPs were evaluated regarding the potential to exclude malignancy: DWIBS (AP1) and subtraction images from the first postcontrast and the unenhanced series (AP2). Diagnostic indexes of both methods were examined by using the McNemar test and were compared with those of the full diagnostic protocol and histopathologic findings.ResultsTwenty-four of 50 participants had a breast carcinoma. With AP1 (DWIBS), the sensitivity was 0.92 (95% confidence interval [CI]: 0.73, 0.98), the specificity was 0.94 (95% CI: 0.77, 0.99), the negative predictive value (NPV) was 0.92 (95% CI: 0.75, 0.99), and the positive predictive value (PPV) was 0.93 (95% CI: 0.75, 0.99). The mean reading time was 29.7 seconds (range, 4.9-110.0 seconds) and was less than 3 seconds (range, 1.2-7.6 seconds) in the absence of suspicious findings on the DWIBS MIPs. With the AP2 protocol, the sensitivity was 0.85 (95% CI: 0.78, 0.95), the specificity was 0.90 (95% CI: 0.72, 0.97), the NPV was 0.87 (95% CI: 0.69, 0.95), the PPV was 0.89 (95% CI: 0.69, 0.97), and the mean reading time was 29.6 seconds (range, 6.0-100.0 seconds).ConclusionUnenhanced diagnostic MR imaging (DWIBS mammography), with an NPV of 0.92 and an acquisition time of less than 7 minutes, could help exclude malignancy in women with suspicious x-ray screening mammograms. The method has the potential to reduce unnecessary invasive procedures and emotional distress for breast cancer screening participants if it is used as a complement after the regular screening clarification procedure.© RSNA, 2015Online supplemental material is available for this article.
Gesehen am 08.05.2019